Monocyte‐Targeting Supramolecular Micellar Assemblies: A Molecular Diagnostic Tool for Atherosclerosis. Issue 3 (22nd August 2014) - Chung, Eun Ji; Mlinar, Laurie B.; Nord, Kathryn; Sugimoto, Matthew J.; Wonder, Emily; Alenghat, Francis J.; Fang, Yun; Tirrell, Matthew
<x xml:space="preserve">Abstract</x> Atherosclerosis is a multifactorial inflammatory disease that can progress silently for decades and result in myocardial infarction, stroke, and death. Diagnostic imaging technologies have made great strides to define the degree of atherosclerotic plaque burden through the severity of arterial stenosis. However, current technologies cannot differentiate more lethal "vulnerable plaques, " and are not sensitive enough for preventive medicine. Imaging early molecular markers and quantifying the extent of disease progression continues to be a major challenge in the field. To this end, monocyte‐targeting, peptide amphiphile micelles (PAMs) are engineered through the incorporation of the chemokine receptor CCR2‐binding motif of monocyte chemoattractant protein‐1 (MCP‐1) and MCP‐1 PAMs are evaluated preclinically as diagnostic tools for atherosclerosis. Monocyte‐targeting is desirable as the influx of monocytes is a marker of early lesions, accumulation of monocytes is linked to atherosclerosis progression, and rupture‐prone plaques have higher numbers of monocytes. MCP‐1 PAMs bind to monocytes in vitro, and MCP‐1 PAMs detect and discriminate between early‐ and late‐stage atherosclerotic aortas. Moreover, MCP‐1 PAMs are found to be eliminated via renal clearance and the mononuclear phagocyte system (MPS) without adverse side effects. Thus, MCP‐1 PAMs are a promising new class of diagnostic agents capable of monitoring the progression of atherosclerosis.